1981
DOI: 10.5962/bhl.title.68699
|View full text |Cite
|
Sign up to set email alerts
|

Forest vegetation removal and slope stability in the Idaho Batholith /

Abstract: A study was conducted on two small watersheds in the Boise National Forest to determine the role of forest vegetation in maintaining more secure slopes in shallow, coarse-textured soils typical of the Idaho batholith. Both soil water piezometry and soil shear strength measurements were made in the watersheds. Results of the field studies and supporting analyses indicate that forest vegetation often provides a critical margin of safety. Woody vegetation growing on slopes of the batholith contributes to stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 11 publications
1
59
0
4
Order By: Relevance
“…Failure becomes more likely upon saturation, often in more prolonged storms and snowmelt (e.g., Reneau and Dietrich, 1987;Gray and Megahan, 1981;Montgomery et al, 2000). In the Payette River and surrounding region, landslides were most common 4-10 years after burning or deforestation (Gray and Megahan, 1981).…”
Section: Postfire Erosion and Deposition: Processes And Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure becomes more likely upon saturation, often in more prolonged storms and snowmelt (e.g., Reneau and Dietrich, 1987;Gray and Megahan, 1981;Montgomery et al, 2000). In the Payette River and surrounding region, landslides were most common 4-10 years after burning or deforestation (Gray and Megahan, 1981).…”
Section: Postfire Erosion and Deposition: Processes And Patternsmentioning
confidence: 99%
“…Although infiltration rates are typically high in unburned areas, postfire surface runoff is greatly enhanced and can readily erode the cohesionless grussy colluvium (Megahan and Molitor, 1975;Robichaud, 2000). Thick colluvium in slope hollows is also prone to landsliding after fires, when tree roots decay and the associated cohesive strength in colluvium is lost (Gray and Megahan, 1981;Clayton and Megahan, 1986;Schmidt et al, 2001).…”
Section: Payette River Study Areamentioning
confidence: 99%
“…The modified shelterwood prescription also left these shelter trees in place for 60 to 90 yr. At this future time, the large trees are cut leaving the number, size, spacing, and crown ratio of large trees the same as specified for the initial harvest. The purpose of this modified shelterwood prescription was to ensure sufficient root mass for mechanically reinforcing and buttressing the soil against shallow landslide occurrence (Gray and Megahan, 1981).…”
Section: Resource Planning In a Rural Areamentioning
confidence: 99%
“…In literature landslides are reported to occur much more frequent (with a maximum up to 350 times) than in virgin forests (Gray and Megahan, 1981;Amaranthus et al, 1985;Larsen and Parks (1997). In future work, the road condition (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a comprehensive survey in the tropics, rate of landslide disturbance is increased from 5 to 8 times in a 170 m wide swath along road corridors (Larsen and Parks, 1997). Other studies reported an 25 to 350 times increase in landslides in forests with small roads compared to pristine forests (Gray and Megahan, 1981;Amaranthus et al, 1985). Documenting landslides provides fundamental information on the landslideprocesses, which is very useful for reducing landslide hazards and risk (Corominas and Moya, 2008).…”
Section: Background and Motivationmentioning
confidence: 99%